(untitled) (Journal of Atomic and Molecular Sciences, 2018)
We study the field entropy squeezing as a measure of the entanglement in a three-level system interacting with a cavity field. Numerical calculations under current experimental conditions are performed and it is found that the initial state setting and atom-field coupling present changes of the general features of the field entropy squeezing dramatically.